Impact of Malocclusions on the Oral Health-Related Quality of Life of Early Adolescents in Ndola, Zambia - Severine N. Anthony; Kayembe Zimba; Balakrishnan Subramanian (International Journal of Dentistry)
The study aimed to assess the prevalence of malocclusions and its impact on oral health-related quality of life (OHRQoL) among early adolescents in Ndola, Zambia. It used a random sample of 384 primary school children aged 12–14 years. The Child Oral Health Impact Profile-Short Form 19 (COHIP-SF19) was used to assess OHRQoL, and the Dental Aesthetic Index (DAI) was used to examine dentofacial anomalies. The chi-square test was used to study whether there was a statistically significant association between variables and multivariate logistic regression for the influence of sociodemographic and malocclusions on OHRQoL. Statistical significance was set at p<0.05. Participants’ sociodemographics were 53.6% female, 41.7% aged 13 years, and 43.5% from grade six. The overall reported impact on OHRQoL was 11.7%, which was significant (p<0.001) by age and sex, and higher in females than males. The overall prevalence of malocclusions was 27.9%, which was significant (p=0.005) by sex, and higher in males than females. Children with malocclusions reported significant (p<0.001) negative oral health impact compared to the children without malocclusions. Spacing, diastema, and crowding were most prevalent malocclusions that showed clear inverse association with OHRQoL. The study findings provide indications that malocclusions are negatively associated with OHRQoL among Zambian early adolescents.